Food Insecurity in Maine Higher Education - McKeage, Kim; Wertheim, Frank; Slovenski, Sally; El-Khalidi, Sumaya (Maine Policy Review, 2021)
In 2017–2018, University of Maine Cooperative Extension and Maine Campus Compact conducted a statewide analysis to assess the extent and subsequent effects of food and housing insecurity within the college student population. A total of 26 higher education institutions (community colleges and private and public four-year colleges and universities) throughout the state of Maine received surveys to investigate food and housing insecurity. This study reports on the findings from the 1,704 completed surveys from 24 of those campuses. We found significant food insecurity among respondents. The results demonstrate how food insecurity relates to institutional, geographic, and student characteristics. We discuss the implications for higher education policy across Maine and practices at individual institutions.